SLAM â Map Building and Navigation via ROS - Pajaziti, Arbnor (International Journal of Intelligent Systems and Applications in Engineering, 2014)
The presented work describes a ROS based control system of a Turtlebot robot for mapping and navigation in indoor environments. It presents the navigation of Turtlebot in self-created environment. The mapping process is done by using the GMapping algorithm, which is an open source algorithm and the localization process is done by using the AMCL pack. There are ROS built functions used in order to perform navigation of Turtlebot. The SLAM method implemented in ROS has proven a way for robots to do localization and mapping autonomously. The aim defined in paper to fulfill mapping, localization and navigation of Turtlebot in new and unknown environment is achieved.